2013
DOI: 10.1007/s11934-013-0325-x
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Versus Continuous Androgen Deprivation Therapy in Advanced Prostate Cancer

Abstract: Intermittent androgen deprivation is increasingly employed as an alternative to continuous life long androgen deprivation therapy for men with advanced or recurrent prostate cancer. Two recent phase III trials have clarified the benefits of intermittent therapy. In men with non-metastatic disease with PSA recurrence after definitive local therapy, intermittent therapy showed equivalent survival to continuous therapy, with significant improvements in quality of life. Patients on intermittent therapy experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It has been suggested that patients who failed to achieve a PSA nadir <4 ng/ml after the induction period of 6 months should not be offered IAD [44]. Factors that influence testosterone recovery also include baseline TT [45]. Our study showed that, in the PCa population, there was a large variation in TT serum levels (range 5.50-40.70 nmol/l; table 1) which was independently associated with FT and pGS (table 4B).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that patients who failed to achieve a PSA nadir <4 ng/ml after the induction period of 6 months should not be offered IAD [44]. Factors that influence testosterone recovery also include baseline TT [45]. Our study showed that, in the PCa population, there was a large variation in TT serum levels (range 5.50-40.70 nmol/l; table 1) which was independently associated with FT and pGS (table 4B).…”
Section: Discussionmentioning
confidence: 99%
“…13 Recent reviews comparing efficacy, side effects, time to castration resistance, overall and cancer-specific survival between intermittent and continuous ADT have been summarised; however, the evidence regarding the tradeoffs between the benefits and risks of intermittent ADT remains inconclusive. [17][18][19][20][21][22][23] Generally the consensus is that overall survival is equivalent between intermittent and continuous ADT in most settings. However, concerns remain with high-risk disease, as one of the larger trials did not meet criteria for non-inferiority of an intermittent regimen in men with metastatic cancer.…”
Section: How Might This Impact On Clinical Practice?mentioning
confidence: 99%
“…Recent studies on the treatment of advanced prostate cancer suggested that intermittent ADT might provide comparable survival to continuous ADT, with significant improvements in QOL (5). There have been considerable arguments regarding the benefit of continuous and maintenance chemotherapy after first response in other solid tumors (6,7).…”
Section: Introductionmentioning
confidence: 99%